Assessing the Role of Ependymal and Vascular Cells as Sources of Extracellular Cues Regulating the Mouse Ventricular-Subventricular Zone Neurogenic Niche - Quaresima, Sabrina; Istiaq, Arif; Jono, Hirofumi; Cacci, Emanuele; Ohta, Kunimasa; Lupo, Giuseppe (Frontiers in Cell and Developmental Biology, 2022)
Neurogenesis persists in selected regions of the adult mouse brain; among them, the ventricular-subventricular zone (V-SVZ) of the lateral ventricles represents a major experimental paradigm due to its conspicuous neurogenic output. Postnatal SVZ neurogenesis is maintained by a resident population of neural stem cells (NSCs). Although V-SVZ NSCs are largely quiescent, they can be activated to enter the cell cycle, self-renew and generate progeny that gives rise to olfactory bulb interneurons. These adult-born neurons integrate into existing circuits to modify cognitive functions in response to external stimuli, but cells shed by V-SVZ NSCs can also reach injured brain regions, suggesting a latent regenerative potential. The V-SVZ is endowed with a specialized microenvironment, which is essential to maintain the proliferative and neurogenic potential of NSCs, and to preserve the NSC pool from exhaustion by finely tuning their quiescent and active states. Intercellular communication is paramount to the stem cell niche properties of the V-SVZ, and several extracellular signals acting in the niche milieu have been identified. An important part of these signals comes from non-neural cell types, such as local vascular cells, ependymal and glial cells. Understanding the crosstalk between NSCs and other niche components may aid therapeutic approaches for neuropathological conditions, since neurodevelopmental disorders, age-related cognitive decline and neurodegenerative diseases have been associated with dysfunctional neurogenic niches. Here, we review recent advances in the study of the complex interactions between V-SVZ NSCs and their cellular niche. We focus on the extracellular cues produced by ependymal and vascular cells that regulate NSC behavior in the postnatal V-SVZ, and discuss the potential implication of these molecular signals in pathological conditions.